How to report economic news - Walton, Nicola (Routledge, an imprint of Taylor & Francis Group, 2017)
"Chapters cover key topics including inflation, monetary policy, labour markets, fiscal policy and residential property markets. The book takes the UK economy as its main focus, but also explores European, US and Japanese markets in depth. In addition, the title explores other major global topics such as the rise of Brazil, Russia, India, China (BRIC) economies and the role of multinational organisations such as the International Monetary Fund."--Provided by publisher.